Nanocomposite films as electrochemical sensors for detection of catalase activity - Johnson, Dwight; Kim, Unyoung; Mobed-Miremadi, Maryam (Frontiers in Molecular Biosciences, 2022)
Transcutaneous films that are equipped with in situ sample collection and sensing offer numerous advantages for diagnosing and treating diseases namely chronic wound healing where oxidoreductase enzymes are the main contributors to regeneration. Among these developments, cross-linked substrates have garnered attention as they simultaneously enable enzymatic reaction in a control volume extended to adsorption of redox capacitors for amplification of electrochemical signals. In this study, the effect of catalase immobilization in mold-casted alginate-based thin films (1 mm x 6 mm x 10 mm) containing multi walled nanotubes (CNT) coated with chitosan have been studied via amperometry. Results indicate that hydrogen peroxide detection is not diffusion-limited by the 100 m thick chitosan layer if the polyelectrolyte is in contact with the sensing carbon electrode, and, the linear detection of the enzyme absent in solution is enabled by immobilization (R2 =0.9615). The amperometric-based sensitivity of 4.55 A/mM for the optimal formulation is comparable to other nanomaterial hybrid sensing solution namely amine-functionalized graphene and electrode-conjugated enzymes. The suitability of the optimized chitosan-coated alginate slabs nano-environment for co-encapsulation of catalase and CNT was confirmed by cyclic voltammetry